2001
DOI: 10.1016/s0166-6851(01)00278-x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme geographical fixation of variation in the Plasmodium falciparum gamete surface protein gene Pfs48/45 compared with microsatellite loci

Abstract: Comparing patterns of genetic variation at multiple loci in the genome of a species can potentially identify loci which are under selection. The large number of polymorphic microsatellites in the malaria parasite Plasmodium falciparum are available markers to screen for selectively important loci. The Pfs48/45 gene on Chromosome 13 encodes an antigenic protein located on the surface of parasite gametes, which is a candidate for a transmission blocking vaccine. Here, genotypic data from 255 P. falciparum isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
40
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 49 publications
12
40
0
Order By: Relevance
“…Molecular genetic data on the present-day populations of P. falciparum support the proposition that they did, indeed, spread from an origin in sub-Saharan Africa (40,41). As already discussed, the evidence from human genetic data imply a West African origin of P. falciparum within the past few thousand years.…”
Section: Out Of Africasupporting
confidence: 62%
“…Molecular genetic data on the present-day populations of P. falciparum support the proposition that they did, indeed, spread from an origin in sub-Saharan Africa (40,41). As already discussed, the evidence from human genetic data imply a West African origin of P. falciparum within the past few thousand years.…”
Section: Out Of Africasupporting
confidence: 62%
“…To have a reference for genetic variation and linkage disequilibrium at neutral regions, the following nine additional STR loci were analyzed: TAA42, TAA81 (chromosome 5), TA1, TAA87, TAA109 (chromosome 6), ARA2 (chromosome 11), TA102, PfPK2, and Pfg377 (chromosome 12) (83,84).…”
Section: Methodsmentioning
confidence: 99%
“…One study testing a panel of sera from Cameroon and the Gambia found sera to have variable TRA against different gametocyte isolates from naturally infected individuals (128). It is unclear if this was due to antigenic variation in parasites, though sequence variation in both Pfs48/45 and Pfs230 appears limited (102,124). Antibody concentration is clearly important.…”
Section: Evidence For Naturally Acquired Transmissionblocking Activitymentioning
confidence: 99%